Music teacher education: Discussion and based on the documentar analysis of European and Latin American programmes - Aróstegui, José Luis; Cisneros-Cohernour, Edith (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
In this paper we present a summary of the major findings discussed in this monograph of the Profesorado journal dedicated to the analysis of the music teacher education programmes accross Europe and Latin America. Our compendium pays attention to the key elements of the programmes, their curriculum approach, the general concept of music education supported. We also discuss the implications that this analysis brings out for the field of music teacher education.